2019
DOI: 10.2166/wst.2020.062
|View full text |Cite
|
Sign up to set email alerts
|

Quick incubation process to determine inactivation of Ascaris and Toxocara eggs

Abstract: Helminth eggs are among the most important biological contaminants in environmental engineering. They pose a significant health risk associated with poor sanitation, the use of contaminated water for irrigation, and the disposal of excreta or sludge to land. Helminths are parasitic worms transmitted to humans via their eggs, which is the infective stage of their life cycle. They are therefore relevant to public health and environmental fields due to their low infectious dose, their persistence in the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…A total number of eggs ranged between 9.96 and 143.54 eggs/g of DM matching the results of other studies for FS produced in the tropical regions (Heinss et al 1998;Yen-Phi et al 2010;Seck et al 2015;Letah Nzouebet et al 2016). In terms of helminth egg species abundance, the predominance of Ascaris lumbricoides eggs as well as the F. hepatica and S. stercoralis can be explained by their high resistance to environmental conditions (Pecson et al 2007;Maya et al 2019) and their prevalence among the population, where the FS samples originated from Letah Nzouebet et al (2016). In order to understand the effects of FS helminth egg variability, the correlation between the physicochemical parameters and the helminth eggs was analyzed.…”
Section: Quality Of the Raw Fs Applied On Bedssupporting
confidence: 81%
“…A total number of eggs ranged between 9.96 and 143.54 eggs/g of DM matching the results of other studies for FS produced in the tropical regions (Heinss et al 1998;Yen-Phi et al 2010;Seck et al 2015;Letah Nzouebet et al 2016). In terms of helminth egg species abundance, the predominance of Ascaris lumbricoides eggs as well as the F. hepatica and S. stercoralis can be explained by their high resistance to environmental conditions (Pecson et al 2007;Maya et al 2019) and their prevalence among the population, where the FS samples originated from Letah Nzouebet et al (2016). In order to understand the effects of FS helminth egg variability, the correlation between the physicochemical parameters and the helminth eggs was analyzed.…”
Section: Quality Of the Raw Fs Applied On Bedssupporting
confidence: 81%
“…A recent study found that at temperatures of 28°C and 34°C, viable Ascaris spp. eggs could develop into larval stages, which made them more infectious, while quick incubation at 60°C for 1 hour could reduce the number of eggs (24). The effect of temperature was also found in research using a solar drying process for sludge with a daily maximum temperature of 40°C -68.8°C can endanger helminth egg viability as it can remove most helminth eggs contained (25).…”
Section: Discussionmentioning
confidence: 89%
“…They cause a group of diseases called "helminthiasis" which are given specific names depending on the genus concerned (for example, ascariasis for the genus Ascaris). [37] mebendazole are donated to national ministries of health through WHO in all endemic countries for the treatment of all school-aged children. Generic ivermectin for S. stercoralis control has been available at an affordable price since 2021.…”
Section: Figure 4 Relative Distributions Of Parasites In the Communitymentioning
confidence: 99%